The Influence of Competence and Work Motivation on Organizational Commitment of Employees in Cimaung District, Bandung Regency - Budiman, Arif; Siddiq, Andhika Mochamad (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study investigates the influence of competence and work motivation on organizational commitment among civil servants in the Cimaung District Office, Bandung Regency. Using a quantitative approach with descriptive and verification methods, the research involved a saturated sample of 42 respondents. Data were collected through structured questionnaires and analyzed using multiple linear regression. The findings reveal that competence has a significant and positive effect on organizational commitment, while work motivation does not show a statistically significant effect when tested independently. Simultaneously, both variables significantly influence commitment, with an R² value of 0.698 indicating that 69.8% of the variation in organizational commitment can be explained by competence and motivation. These results underscore the importance of aligning employee skills and capabilities with job requirements and suggest that competency development should be prioritized in human resource strategies for public institutions. Further research is recommended to explore additional factors such as leadership style and organizational climate.